IMHOTEP: cross-professional evaluation of a three-dimensional virtual reality system for interactive surgical operation planning, tumor board discussion and immersive training for complex liver surgery in a head-mounted display - Kenngott, Hannes Götz; Pfeiffer, Micha; Preukschas, Anas; Bettscheider, Lisa Paulina; Wise, Philipp; Wagner, Martin; Speidel, Stefanie; Huber, Matthias Christoph; Nickel, Felix; Mehrabi, Arianeb; Müller, Beat P. (Surgical endoscopy and other interventional techniques, 2022)
Virtual reality (VR) with head-mounted displays (HMD) may improve medical training and patient care by improving display and integration of different types of information. The aim of this study was to evaluate among different healthcare professions the potential of an interactive and immersive VR environment for liver surgery that integrates all relevant patient data from different sources needed for planning and training of procedures.